2016
DOI: 10.1002/chem.201601161
|View full text |Cite
|
Sign up to set email alerts
|

Highly Phosphorescent Crystals of Square‐Planar Platinum Complexes with Chiral Organometallic Linkers: Homochiral versus Heterochiral Arrangements, Induced Circular Dichroism, and TD‐DFT Calculations

Abstract: A novel class of chiral luminescent square-planar platinum complexes with a π-bonded chiral thioquinonoid ligand is described. Remarkably the presence of this chiral organometallic ligand controls the aggregation of this square planar luminophor and imposes a homo- or hetero-chiral arrangement at the supramolecular level, displaying non-covalent Pt-Pt and π-π interactions. Interestingly these complexes are highly luminescent in the crystalline state and their photophysical properties can be traced to their agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Chirality is often an intrinsic feature for facial and meridional tris‐cyclometalated Ir III complexes . For square‐planar Pt II complexes, however, such metal‐induced chirality is infrequent, and thus the common way to introduce chirality is to utilize chiral ligands (Scheme ) . Moreover, redshifting emission, either CPL or AIP, into the near‐infrared “imaging window” (650–1000 nm) is still a very challenging and arduous task …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chirality is often an intrinsic feature for facial and meridional tris‐cyclometalated Ir III complexes . For square‐planar Pt II complexes, however, such metal‐induced chirality is infrequent, and thus the common way to introduce chirality is to utilize chiral ligands (Scheme ) . Moreover, redshifting emission, either CPL or AIP, into the near‐infrared “imaging window” (650–1000 nm) is still a very challenging and arduous task …”
Section: Methodsmentioning
confidence: 99%
“…[34,35] For square-planar Pt II complexes, however,s uch metal-induced chirality is infrequent, [18,37,38] and thus the common way to introduce chirality is to utilize chiral ligands (Scheme 1). [24,[39][40][41][42][43][44][45][46] Moreover,r edshifting emission, eitherC PL or AIP, [17,19] into the near-infrared "imaging window" (650-1000 nm) is still av ery challenging and arduoustask. [6] 1,1'-binaphthyls, [1,1'-binaphthalene]-2,2'-diol (BINOL) and [1,1'-binaphthalene]-2,2'-diamine (BINAM), represent ac lass of important chiral molecules that have found extensive applications in fluorescent chiral recognition [51][52][53] anda symmetric synthesis.…”
mentioning
confidence: 99%
“…21 On the other hand some of us demonstrated that enantiopure Pt(terpy) complexes containing chiral organometallic ligands display different emission properties in the solid state when compared to their corresponding racemic species. 22 In previous work we designed a family of lumines-cent cyclometalated iridium compounds with N-heterocyclic carbene ligands attached to an organic naphthalimide chromophore. 23,24 All complexes were deep red emitters (CIE 1931 0.71, 0.29) with good quantum yields, long lifetimes in liquid solution at room temperature and displayed broad emission bands extending beyond 700 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Such compounds are stable and promote metal-metal, and πÀ π interactions, that profoundly impact the properties of the electronic excited states. [3][4][5][6][7][8] Mononuclear platinum(II) complexes with (N^N^N), [3,5,[9][10][11][12][13][14][15][16] (N^C^N) [2,8,[17][18][19] and (C^N^N) [6,[20][21][22][23][24][25][26][27][28][29] pincer-type ligands were prepared and their luminescent properties have been tuned by modifying the nature and the electronic properties of the coordinating tridentate unit and the co-ligand as well. [17][18][25][26] Moreover, the ability of these platinum chromophores to display metal-metal interactions offers an additional strategy to construct supramolecular assemblies and control their formation in presence of external stimuli in solution state.…”
Section: Introductionmentioning
confidence: 99%